An Approach of Software Requirements Elicitation Based on Activity Theory - Martins, Luiz Eduardo Galvão; Daltrini, Beatriz Mascia (Anais Estendidos do Simpósio Brasileiro de Engenharia de Software (SBES), 2000)
The goal of this work is to show an approach of software requirements elicitation based on Activity Theory. This theory has been developed in the psychology area and takes into account several important elements to analyze the context where people perform their actions. Considering the activity as unit of analysis the Activity Theory offers an interesting framework to structuring and organizing the actions performed by the system stakeholders. We intend to use this framework to help in the discovery and capture of software requirements.